2020
DOI: 10.1002/cncr.32787
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus‐avoidance whole‐brain radiation therapy with a simultaneous integrated boost for multiple brain metastases

Abstract: BACKGROUND:The current study was aimed at investigating the feasibility of hippocampus-avoidance whole-brain radiation therapy with a simultaneous integrated boost (HA-WBRT+SIB) for metastases and at assessing tumor control in comparison with conventional whole-brain radiation therapy (WBRT) in patients with multiple brain metastases. METHODS: Between August 2012 and December 2016, 66 patients were treated within a monocentric feasibility trial with HA-WBRT+SIB: hippocampus-avoidance WBRT (30 Gy in 12 fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 37 publications
5
38
2
Order By: Relevance
“…Several studies have shown that higher doses to target lesions could improve on local control rates and potentially reduce intracranial failure [ 9 , 20 , 23 ]. In turn, improving intracranial control could possibly result in improved performance status and reduced neurological death [ 8 , 9 , 12 ]. It would thus seem reasonable to consider giving tumours a simultaneous higher dose during HA-WBRT using HA-SIB-WBRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that higher doses to target lesions could improve on local control rates and potentially reduce intracranial failure [ 9 , 20 , 23 ]. In turn, improving intracranial control could possibly result in improved performance status and reduced neurological death [ 8 , 9 , 12 ]. It would thus seem reasonable to consider giving tumours a simultaneous higher dose during HA-WBRT using HA-SIB-WBRT.…”
Section: Discussionmentioning
confidence: 99%
“…The reported intracranial PFS was noted to be as high as 13.5 months with few ≥Grade 3 toxicities (≤6.5%), making it a potentially viable option. In a propensity score-matched comparison against WBRT, Popp et al reported significantly improved local tumour control rates, intracranial PFS, reduction in neurological deaths and even better OS [ 12 ]. This has led the group to continue to a phase II HIPPORAD Trial comparing HA-WBRT+SIB against WBRT+SIB (German Clinical Trials Registry: DRKS00004598) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…One criticism of typical WBRT is poor local control of existing brain metastases after 30 Gy. A recent single-arm feasibility study investigated the utility of a simultaneous integrated boost (SIB) technique with WBRT [ 21 ]. The investigators prescribed 30 Gy in 12 fractions to the brain and simultaneously boosted metastases and resection cavities to 42 or 51 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Hopefully the open question regarding the role of hippocampal avoidance in PCI will be settled by ongoing trials ( Table 2). Another option that may improve both local and distant brain control could be adding a simultaneous integrated boost with WBRT, although recent trials have excluded SCLC [47]. ICIs with CNS efficacy either alone or in combination with RT were also discussed, although existing data is mainly from preclinical and NSCLC studies and ongoing SCLC trials are limited ( Table 2).…”
Section: Discussionmentioning
confidence: 99%